2000
DOI: 10.1590/s0074-02762000000100023
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of arthropods associated with pig carrion and human corpses in Southeastern Brazil

Abstract: Necrophagous insects, mainly Diptera and Coleoptera, are attracted to specific stages of carcass decomposition, in a process of faunistic succession. They are very important in estimating the postmortem interval, the time interval between the death and the discovery of the body. In studies done with pig carcasses exposed to natural conditions in an urban forest (Santa Genebra Reservation) Key words: forensic entomology -Diptera -Coleoptera -carrion insects -decomposition -death timeThe decomposition of a dead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
1
48

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(196 citation statements)
references
References 5 publications
10
114
1
48
Order By: Relevance
“…The published Brazilian studies on forensic ecological communities, that used domestic pigs as models, also used pseudoreplicates (CarvalhO et al 2000;CarvalhO et al 2001CarvalhO et al , 2004marChiOri et al 2000;Oliveira-da-silva et al (2006);BarBOsa et al 2010;Biavati et al 2010;Mise et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The published Brazilian studies on forensic ecological communities, that used domestic pigs as models, also used pseudoreplicates (CarvalhO et al 2000;CarvalhO et al 2001CarvalhO et al , 2004marChiOri et al 2000;Oliveira-da-silva et al (2006);BarBOsa et al 2010;Biavati et al 2010;Mise et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Souza & Linhares (1997) coletaram adultos de N. rufipes nos estágios de putrefação, putrefação escura e fermentação butírica, durante um ano, em Sus scrofa, em Campinas, Brasil. Carvalho et al (2000) coletaram essa espécie em cadáveres humanos no Instituto de Medicina Legal de Campinas, de 1993 a 1998. Essa mesma espécie foi capturada por Wolff et al (2001), em Medellín, Colômbia, usando Sus scrofa como substrato, nos estágios avançado e seco.…”
Section: Methodsunclassified
“…In Brasil, Moura et al [5] found adults and larvae of O. discicolle in rat carrion in the state of Paraná; Carvalho et al [6] found larvae of O. discicolle in pig carrion in the state of São Paulo. In Colombia, only adults of O. discicolle have been reported; Barreto et al [7] registered the species in human corpses in Cali; and Wolff et al [8] in pig carrion in Medellín.…”
Section: Introductionmentioning
confidence: 99%